High Contrast : Race and Gender in Contemporary Hollywood Films - Willis, Sharon, 1955- (Book collections on Project MUSE., 1997)
In High Contrast, Sharon Willis examines the dynamic relationships between racial and sexual difference in Hollywood film from the 1980s and 1990s. Seizing on the way these differences are accentuated, sensationalized, and eroticized on the screen - most often with little apparent regard for the political context in which they operate - Willis restores that context through close readings of a range of movies from cinematic blockbusters to the work of the new auteurs, Spike Lee, David Lynch, and Quentin Tarantino.